Moving forward the future of consumer credit and mortgage finance - Retsinas, Nicolas Paul 1946-; Belsky, Eric S. (Joint Center for Housing Studies, Harvard University, 2011)
"Explores what caused the housing and mortgage crisis and provides remedies to repair the damage to ensure fairness, protect consumers, and guarantee soundness of the financial system without stifling innovation and overly restricting access to credit and consumer choice"--Provided by publisher.